Comprehensive proteomic characterization of urethral stricture disease in the Chinese population - Gao, Jiangtao; Liu, Hui; Li, Lingling; Guo, Chunmei; Wang, Zhiyong; Cheng, Mengya; Tan, Subei; Chen, Lu; Shi, Jijing; Wu, Hui; Feng, Chao; Yu, Guoying; et al. (Frontiers in Molecular Biosciences, 2024)
Background Male urethral stricture disease (USD) is predominantly characterized by scar formation.There is still lack of effective therapeutic drugs, and comprehensive molecular characterizations of USD formation are undefined yet.Methods Proteomic profiling of twelve scar tissues and five matched normal adjacent tissues (NATs).Proteomic analysis methods were applied to explore the molecular characterizations of USD formation, including uncovering mechanistic pathways and providing novel biomarkers for scar formation.Comparative proteomic analysis showed that the extracellular matrix (ECM) and complement cascade signaling were predominant in scar tissues. COL11A1 and CD248 significantly contributed to the accumulation of ECM components. Our study presented diverse molecular mechanism of scar formation across different ages, and suggested the potential effects of PXK in the Age 1 (< 45) patients.Furthermore, immune infiltration studies indicated the therapeutic potential of inhibiting the complement system (C4A, C4B) in the Age 2 (≥ 45) patients, providing potential strategy for USD in the clinic.This study illustrated the pathogenesis of USD formation, and the diverse characteristics of USD patients with different ages, enhancing our understanding of the disease's pathogenesis and providing a valuable resource for USD.